Application of the Transmission Line Method to Calculate the Energy Bands for an Electron in One Dimensional Lattice - Alhrari, Hawa M.; Elgweri, Huwaida K.; Mansor, Mohamed (The Libyan Journal of Science, 2020)
In this paper, we calculate the energy bands for an electron in one dimensional lattice, by solving Schrödinger equation for a periodic potential using the transmission line method. In this technique we use the impedance function, which gives information about the physics of the problem through its relation to the wave function, and from the impedance we can also compute the energy eigenvalues. Comparison of the numerical solutions obtained by the transmission line method with exact solutions and numerical solutions obtained by other methods demonstrates the accuracy of this method.